PERLINDUNGAN HUKUM TERHADAP PENCIPTA ATAU PEMEGANG HAK CIPTA LAGU DALAM PEMBAYARAN ROYALTI - Situmeang, Ampuan; Kusmayanti, Rita (Journal of Law and Policy Transformation, 2020)
Intellectual property is the result of a work for an author that has exclusive rights that only exist and are attached to the owner or bearer of rights of a work. Other parties craving to use or use the copyright need to create or produce the work required in obtain the author's permission. The problems in this research were how is the legal protection for the creator or copyright holder of the song to the payment of royalties and how to complete the objection to approve the use of the song without paying royalties. This research used normative research methods. Normative research is research on literature or document studies that support secondary research. Data collection from the results of the study was then analyzed by the author by qualitative-descriptive. Which is the type of research that aims to obtain about how the use of exclusive rights to economic rights that are still not properly implemented which requires an increase in the Author or the Copyright Holder. Based on the research results and discussion, it can be concluded the use of exclusive rights to economic rights that are still not properly implemented which requires an increase in the Author or the Copyright Holder. The formation of LMKN is a form of protection given by the Government to the copyright of songs given also provides tariffs on royalties that must be agreed by the User. Dispute resolution can be done through litigation and non-litigation. Dispute resolution involving different countries can be done through the WIPO Arbitration and Meditation Center.